A combined catalyst, preparation method, application and method for preparing p-hydroxybenzaldehyde by catalytic oxidation of p-methylphenol under non-alkali conditions

CN119215931BActive Publication Date: 2026-10-20QILU UNIVERSITY OF TECHNOLOGY (SHANDONG ACADEMY OF SCIENCES)
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411417747.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2026-10-20
Estimated Expiration
2044-10-11

AI Technical Summary

Technical Problem

[0008]有鉴于此,本发明的目的在于提供一种组合催化剂、制备方法、应用及非碱条件催化氧化对甲基苯酚制备对羟基苯甲醛的方法,以解决现有催化对甲酚制备对羟醛工艺过程中存在的产物产率低、需要加入大量可溶性碱和催化剂易中毒的问题,以及所用有机溶剂易燃易爆的问题

Benefits of technology

本发明的组合催化剂,由PtFe/C层间有序纳米合金催化剂和不同粒径的Pd基催化剂构建而成,组合催化剂中的Pd亚纳米团簇催化剂能够提供丰富的催化位点,确保金属原子的利用效率最大化;高度分散的亚纳米全暴露团簇使得所有金属原子完全暴露,从而可用于吸附和转化反应物,显著提升了Pd催化剂中活性中心的效率;通过调控活性中心的原子结构和电子结构,该催化剂实现了氧气的高效还原活化,并对底物及各级中间体进行了适当的吸附;各级氧化步骤协同增效,表现出了优异的活性和稳定性。且组合催化剂在循环利用下仍使得原料和产物保持较高的转化率和产率,表现出了优异的稳定性,成功实现了对甲酚高选择性制备对羟醛;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119215931B_ABST
    Figure CN119215931B_ABST
Patent Text Reader

Abstract

The present application relates to a kind of combination catalyst, preparation method, application and the method for preparing p-hydroxybenzaldehyde by catalytic oxidation of p-methylphenol under non-base condition.The combination catalyst is composed of PtFe / C catalyst and Pd / C catalyst or Pd / S-C catalyst.The present application also provides the preparation method of combination catalyst, including: iron salt and pyridine are mixed, add platinum acid and carbon source, obtain PtFe / C and Pd / C catalyst mixture;Or mesoporous S-C carrier is dissolved in water, add palladium salt, heat treatment, obtain Pd / S-C catalyst.The present application also provides the combination catalyst for catalytic preparation of p-hydroxyaldehyde.The present application also provides a kind of preparation method of p-hydroxyaldehyde, including: adding p-cresol and combination catalyst to non-basic solvent, heat reaction, obtain p-hydroxyaldehyde.The present application solves the problem that existing p-hydroxyaldehyde preparation process is seriously dependent on alkaline reaction environment and the problems that product yield is low and catalyst is easily poisoned in p-hydroxyaldehyde preparation process under non-base condition.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of p-hydroxyaldehyde preparation technology, specifically to a combined catalyst, preparation method, application, and a method for preparing p-hydroxybenzaldehyde by catalytic oxidation of p-methylphenol under non-alkaline conditions. Background Technology

[0002] The oxidation of p-cresol (hereinafter referred to as p-cresol) is of significant importance in the industrial field. Its main oxidation product, such as p-hydroxybenzaldehyde (hereinafter referred to as p-hydroxyaldehyde), has a wide range of industrial applications. It is a key intermediate in the production of vanillin (a widely used flavoring agent), trimethoxybenzaldehyde, various agricultural chemicals, and semi-synthetic drugs such as penicillin, amoxicillin, and trimethoxybenzamide. In addition, p-hydroxyaldehyde can also be used as a whitening agent in metal electroplating, and as an additive in perfumes and liquid crystals, showing broad application potential. Typical methods for synthesizing p-hydroxyaldehyde from p-cresol include p-toluene esterification, Mn2O3 oxidation, transition metal salt catalytic oxidation, Etard oxidation, and electrochemical oxidation. Currently, the most cost-effective method is the transition metal salt catalytic oxidation method.

[0003] Transition metal catalytic oxidation methods, such as those using cobalt (Co) salts as homogeneous or heterogeneous catalysts, or nano-alloy composite catalysts formed by cobalt salts and manganese (Mn), copper (Cu), and cerium (Ce), as well as metalloporphyrin catalysts (such as iron-based and cobalt-based porphyrins), typically use methanol as the reaction solvent. In the reaction system, a strong base (usually sodium hydroxide) equivalent to 2.5 to 5 times the substrate is added to activate p-cresol, converting it to phenolate. Under oxygen or flowing air conditions, and with appropriate reaction temperature and residence time, the reaction can be completed to produce p-hydroxyl. The selectivity and yield of the product are typically between 70% and 95%; however, other byproducts are mainly tar formed from p-cresol dimers or polymers, which poses significant challenges to the separation of the target product and easily adsorbs onto the catalyst surface, leading to catalyst poisoning, reduced catalytic activity, or even complete loss of catalytic activity.

[0004] In an alkaline ethylene glycol reaction solvent, researchers used either a cobalt chloride homogeneous catalyst or a cobalt-copper nanoalloy heterogeneous catalyst. With three times the amount of sodium hydroxide added as p-cresol, and using flowing oxygen at a rate of 40 mL / min as the oxidant, a batch reaction was conducted at 100 °C for 18 hours. The highest yield of p-hydroxyl was achieved at 74.8%. Other byproducts, primarily tar formed from p-cresol dimers or polymers, posed significant challenges to the separation of the target product and were easily adsorbed onto the catalyst surface, leading to catalyst poisoning, reduced catalytic activity, or even complete loss of catalytic activity.

[0005] A batch reaction study was conducted for 24 hours in an acidic ethylene glycol reaction solvent (a mixture of 30% acetic acid and 70% ethylene glycol), using commercially available 5wt% Pd / C as a catalyst, a flowing oxygen atmosphere of 40 mL / min, and at 100 °C. Under optimal reaction conditions, a 73.9% conversion of p-cresol and a 52.7% yield of p-hydroxyaldehyde were achieved. Other byproducts included small amounts of p-cresol oxidation intermediates (1–2% p-hydroxybenzyl alcohol), over-oxidation products (3.8% p-hydroxybenzoic acid), ether compounds formed from p-cresol and ethylene glycol (15–50%), and tar-like substances formed from p-cresol dimers and polymers, which were difficult to measure. However, these tar-like substances significantly poisoned the catalyst and caused considerable difficulties in product separation.

[0006] Using a 50 wt.% aqueous acetic acid solution as the reaction solution and Pt / C, Pd / C, or palladium acetate as catalysts, a 100% conversion of p-cresol was achieved in the catalytic oxidation to p-hydroxyl. However, the highest yield of p-hydroxyl was only 35%, with most of the p-cresol undergoing dimerization or polymerization, ultimately existing as tar. This is because the Pt / C, Pd / C, or palladium acetate combinations exhibit low catalyst selectivity, leading to severe side reactions. The catalyst is rapidly adsorbed by the generated tar, further deactivating it. This demonstrates that Pt and Pd combined catalysts possess certain catalytic activity, but exhibit very low selectivity for the target product.

[0007] Furthermore, the oxidation reaction starting from p-cresol in the existing process for preparing p-hydroxyl still faces several challenges: 1) Although methanol is a commonly used reaction solvent in laboratory research and industrial production due to its low viscosity, high oxygen solubility, and low boiling point, it is a flammable, explosive, and low-boiling-point organic solvent. The explosion limit of methanol is approximately between 6% and 36.5%, posing significant safety hazards under aerobic and high-temperature catalytic oxidation conditions; 2) In the reaction system for the highly selective catalytic oxidation of p-cresol to prepare p-hydroxyl, an excess of soluble base (2.5-5 times the equivalent of the substrate) is usually required. This not only requires the reaction equipment to have alkali corrosion resistance but also places higher demands on the stability of the catalyst in strongly alkaline solutions. The target product exists in the form of a sodium salt. To obtain p-hydroxyl, an excess of acid must be used to neutralize the base in the reaction system and convert the sodium salt form of p-hydroxyl into the product. This process generates excessive amounts of low-value waste salt, increasing the complexity of the product manufacturing process and raising production costs; 3) The selectivity for aldol is typically between 70-95%, and the generation of byproducts requires separation through distillation, extraction, or combinations thereof (such as extractive distillation, azeotropic distillation, etc.), making the subsequent separation and purification of products difficult and costly. In particular, the generation of reactant dimers and tar during catalytic oxidation poses even greater challenges to product separation and purification. The excess soluble base introduced into the reaction system increases the number and complexity of reaction separation components, further increasing the cost of product purification steps, thereby increasing the production cost of aldol; 4) Existing transition metal catalysts, such as Co, Cu, Ce, or combinations thereof, have low activity, leading to increased reaction temperatures, prolonged reaction times, and reduced selectivity of the target product for aldol, which is also one of the reasons for the high separation costs. Limited catalyst activity leads to increased catalytic conversion frequency, resulting in higher equipment investment; 5) In systems using commercially available Pd / C (5 wt.%) as a catalyst, the high dosage and price of Pd, a precious metal, result in limited activity and a significant risk of spontaneous combustion. Direct use of Pd / C in organic solvent mixtures (such as ethylene glycol-acetic acid mixtures) carries a high risk of explosion. In pure Pd / C catalytic systems, the activity and selectivity of Pd / C are low, leading to a large amount (20-50 mol.%) of direct ether formation byproducts between p-cresol and ethylene glycol. Existing Pt / C and Pd / C combined catalysts exhibit excessively low catalytic selectivity, generating too much tar products, resulting in poor selectivity for the target product and difficulties in separating it. Ether products or tar byproducts readily adsorb onto the surface of heterogeneous catalysts, leading to catalyst poisoning, reduced activity, or even complete loss of activity. Summary of the Invention

[0008] In view of this, the purpose of the present invention is to provide a combined catalyst, preparation method, application, and a method for the catalytic oxidation of p-cresol to p-hydroxybenzaldehyde under non-alkaline conditions, so as to solve the problems of low product yield, the need to add a large amount of soluble base and easy catalyst poisoning in the existing catalytic process for the preparation of p-hydroxybenzaldehyde from p-cresol, as well as the problems of flammable and explosive organic solvents used.

[0009] The objective problems existing in the current p-cresol catalytic oxidation process are as follows: (1) It is necessary to use methanol solvent, which is flammable and explosive; (2) It is necessary to use an excess of soluble base to ensure the conversion rate of p-cresol and the selectivity of aldol; (3) Under acidic conditions, the selectivity of Pt / C and Pd / C is low, the yield of aldol is too low, and the amount of tar produced is large, and the catalyst is easy to deactivate; (4) Ordinary Pd / C catalysts use a large amount of precious metal Pd, which is costly and poses a flammability risk in organic oxidation systems.

[0010] The technical solution adopted in this invention is as follows: A combined catalyst, consisting of a PtFe / C catalyst and a Pd / C catalyst, or consisting of a PtFe / C catalyst and a Pd / SC catalyst.

[0011] Wherein, Pt represents platinum, Fe represents iron, C represents carbon, Pd represents palladium, and S represents sulfur.

[0012] Preferably, the PtFe / C catalyst is an ordered nano-alloy catalyst.

[0013] Preferably, the Pd / SC catalyst is selected from Pd1 / SC catalyst (Pd single atom), Pd NC / SC catalyst (fully exposed Pd nanoclusters) and Pd NP At least one of / SC catalysts (Pd nanoparticles).

[0014] Preferably, the mass ratio of the PtFe / C catalyst to the Pd / C catalyst is 5:1 to 1:5.

[0015] Preferably, the mass ratio of the PtFe / C catalyst to the Pd / SC catalyst is 5:1 to 1:5.

[0016] Wherein, Pd1 represents a single Pd atom; Pd NC This represents fully exposed subnanometer clusters of Pd; Pd NP This indicates Pd nanoparticles. The loading of Pd1 / SC catalyst is controllable from 1 wt.% to 5 wt.%, Pd NC / SC catalyst and Pd NP The particle size of / SC catalysts is controllable.

[0017] This invention also provides a method for preparing a combined catalyst, comprising the following steps: Iron salts are dissolved in water to obtain an iron salt solution; The pyridine compound is dissolved in an organic solvent to obtain a pyridine solution; The iron salt solution and the pyridine solution were mixed to obtain the complex solution; Platinum acid solution was added to the complex solution to obtain the PtFe compound; PtFe compounds were dispersed in water, then a carbon source was added, the mixture was dried, and subjected to a first heat treatment to obtain a PtFe / C catalyst. By mixing the PtFe / C catalyst with the Pd / C catalyst, a combined catalyst is obtained.

[0018] This invention also provides a method for preparing a combined catalyst, comprising the following steps: Mesoscopic SC supports were obtained by using a cobalt-assisted carbonization molecular precursor system. The mesoscopic SC support was dispersed in water, and a palladium salt solution was added to obtain the precursor; The precursor was subjected to a second heat treatment to obtain the Pd / SC catalyst.

[0019] Palladium fully exposed sub-nanoclusters and nanoparticle catalysts with different palladium single-atom loadings and particle size distributions were prepared using an efficient and convenient method. In particular, the Pd fully exposed sub-nanocluster catalyst exhibited the highest Pd atom utilization rate and the highest Pd-atom-based catalytic conversion frequency, and constructed surface active sites with optimal energy level matching for the adsorption and conversion of specific reactants / intermediates. This characteristic significantly improved the efficiency of the palladium active centers in the catalyst, thereby enhancing the activity of the catalytic reaction.

[0020] Preferably, the pyridine compound is selected from at least one of pyridine, 2,2'-bipyridine, and 2,2':6',2''-tripyridine.

[0021] Preferably, the iron salt is selected from at least one of ferrous sulfate, ferrous chloride, ferrous nitrate, and ferrous sulfate heptahydrate.

[0022] Preferably, the carbon source is selected from commercially available activated carbon or carbon material carrier.

[0023] Preferably, the platinum acid solution is selected from at least one of chloroplatinic acid solution, chloroplatinic acid hexahydrate, and potassium chloroplatinate solution.

[0024] Preferably, the temperature of the first heat treatment is 500 ℃ to 900 ℃, the heating method is programmed heating, and the heating rate is 5 ℃ / min to 10 ℃ / min; the time of the first heat treatment is 3 h to 6 h; and the first heat treatment is carried out in a mixed atmosphere of hydrogen and inert gas.

[0025] Preferably, the temperature of the first heat treatment is 700 °C, the heating method is programmed heating, and the heating rate is 5 °C / min. The duration of the first heat treatment is 6 h.

[0026] Preferably, the organic solvent is selected from ethanol.

[0027] Preferably, the method for preparing the mesoscopic SC support includes the following steps: adding 2,2-dithiophene, silicon dioxide and cobalt salt to a tetrahydrofuran solution, mixing and drying to obtain a powder; heating and carbonizing the powder, performing alkaline etching and a third heat treatment, and drying to obtain the mesoscopic SC support.

[0028] Preferably, the method for preparing the mesoscopic SC support includes the following steps: adding 2,2-dithiophene, silicon dioxide, and cobalt salt to a tetrahydrofuran solution, stirring at room temperature for 6 hours to form a homogeneous mixture, then removing the solvent by rotary evaporation to obtain a powder; carbonizing the powder at 800 °C, a heating rate of 5 °C / min, and under a N2 atmosphere for 2 hours; etching the carbonized product with 2 M NaOH alkaline solution for 3 days; continuously heating with 0.5 M H2SO4 at 90 °C for 6 hours, and drying overnight at 85 °C to obtain the mesoscopic SC support.

[0029] Preferably, the palladium salt is selected from at least one of palladium chloride, palladium nitrate, and palladium acetate.

[0030] Preferably, the temperature of the second heat treatment is 250℃~500℃, the heating method is programmed heating, and the heating rate is 5℃ / min~10℃ / min.

[0031] Preferably, the precursor is treated at 500°C for 3 hours in a mixed atmosphere of hydrogen and inert gas to obtain Pd. NP / SC catalyst; the heating method is programmed heating, and the heating rate is 5 ℃ / min.

[0032] Preferably, the precursor is treated at 450°C for 3 hours in a mixed atmosphere of hydrogen and inert gas to obtain Pd. NP / SC catalyst; the heating method is programmed heating, and the heating rate is 5 ℃ / min.

[0033] Preferably, the precursor is treated at 350°C for 3 hours in a mixed atmosphere of hydrogen and inert gas to obtain Pd. NC / SC catalyst; the heating method is programmed heating, and the heating rate is 5 ℃ / min.

[0034] Preferably, the precursor is subjected to a heat treatment at 250°C for 2 h in a mixed atmosphere of hydrogen and inert gas to obtain the Pd1 / SC catalyst; the heating method is a programmed temperature rise with a heating rate of 5 °C / min.

[0035] PtFe / C catalyst with Pd single atom Pd1 / SC and Pd fully exposed sub-nano clusters Pd NC / SC, Pd nanoparticles Pd NP The synergistic effect of the / SC combined catalyst promotes oxygen reduction and activation, achieving precise adsorption control of intermediates at active sites and synergistic effects at each oxidation step. This combination of innovative technologies makes it possible to efficiently, safely, and selectively catalyze the oxidation of p-cresol to p-hydroxyl under completely non-alkaline conditions. Laboratory tests verified the effectiveness and stability of this catalyst in both batch and continuous catalytic oxidation processes.

[0036] The present invention also provides an application of a combined catalyst for catalyzing the preparation of p-hydroxyaldehyde from p-cresol.

[0037] This invention also provides a method for preparing p-hydroxyl by non-alkaline catalytic oxidation of p-methylphenol, comprising the following steps: p-Cresol and the combined catalyst described in this invention are added to a mixed solvent that does not contain methanol or soluble base. The mixture is then charged with 0.5 MPa of oxygen or air, heated, and maintained at 70 ℃-100 ℃ for 3-6 h before sampling and analysis to obtain p-hydroxyaldehyde.

[0038] Based on the above-mentioned technical means, the combined catalyst of this invention is used to catalyze the preparation of p-hydroxyl under completely non-alkaline conditions, achieving highly efficient catalytic oxidation of p-cresol to p-hydroxyl. Under completely alkaline conditions, this catalyst can efficiently catalyze the oxidation of p-cresol to p-hydroxyl. This process is not only safe and stable but also highly efficient. From the perspective of atomic structure, this invention constructs an interlayer ordered PtFe nanoalloy (PtFe / C), thereby precisely controlling the atomic structure and electronic structure of the active center of the heterogeneous supported PtFe nanoalloy catalyst. This allows for the construction of electronic energy states that are more matched with the antibonding orbital energy levels of the activated substrate molecule O2 during the catalytic oxidation process, while ensuring appropriate adsorption of reaction substrates (such as p-cresol, phenoxy radicals, and benzyloxy radicals), thereby promoting the efficient reduction and activation of O2 molecules and their participation in various stages of the p-cresol oxidation process.

[0039] Regarding Pd-based catalysts, this invention prepared palladium single atoms, fully exposed palladium sub-nanoclusters, and palladium nanoparticle catalysts with controllable particle size, all with loadings ranging from 1.0 wt.% to 5.0 wt.%. Unlike the "top-down adsorption" of O2 molecules by Pd1 sites in Pd1 / SC, the Pd sites in fully exposed Pd sub-nanoclusters or Pd nanoparticles provide a more favorable "bridging adsorption" form of O2, offering higher O2 adsorption and reduction activation activities. In particular, the fully exposed Pd sub-nanocluster catalyst, with its catalytic sites providing nearly 100% Pd atom utilization efficiency, significantly improves the catalytic conversion frequency and catalytic activity of the Pd active centers in the Pd catalyst.

[0040] By combining PtFe / C and Pd-based catalysts with different particle size distributions, this invention achieves the catalytic oxidation of p-cresol to p-hydroxyl under completely alkali-free conditions in an aqueous reaction medium. Within a short reaction time, the conversion rate of p-cresol can reach 100%, and the yield of p-hydroxyl exceeds 99%. In batch operation, the selectivity of the target product did not significantly decrease after five catalyst cycles. In a continuous flow reactor using continuously flowing air as the oxidant, this catalytic system further achieves the continuous production of p-hydroxyl with high selectivity from p-cresol. During continuous oxidation, the selectivity of the target product for p-hydroxyl at the reactor outlet remains above 91% for 72 hours, and the catalyst shows no significant deactivation during continuous use for 72 hours.

[0041] Preferably, the methanol-free organic solvent is selected from at least one of ethylene glycol, acetic acid, and acetonitrile.

[0042] Preferably, the methanol-free organic solvent is selected from a mixture of ethylene glycol, acetic acid, and water.

[0043] Preferably, the methanol-free organic solvent is selected from a mixture of acetonitrile, acetic acid, and water.

[0044] The present invention also provides a p-hydroxyaldehyde prepared by the preparation method described in the present invention.

[0045] The beneficial effects of this invention are: The combined catalyst of this invention is constructed from a PtFe / C interlayer ordered nanoalloy catalyst and Pd-based catalysts of different particle sizes. The Pd sub-nano cluster catalyst in the combined catalyst provides abundant catalytic sites, ensuring maximum utilization efficiency of metal atoms. The highly dispersed, fully exposed sub-nano clusters ensure complete exposure of all metal atoms, allowing for adsorption and conversion of reactants, significantly improving the efficiency of the active centers in the Pd catalyst. By controlling the atomic and electronic structures of the active centers, this catalyst achieves efficient reduction and activation of oxygen and appropriate adsorption of substrates and intermediates at each stage. The synergistic effect of each oxidation step demonstrates excellent activity and stability. Furthermore, the combined catalyst maintains high conversion rates and yields of feedstocks and products even under recycling conditions, exhibiting excellent stability and successfully achieving highly selective preparation of p-hydroxyaldehyde from p-cresol. The present invention discloses a method for preparing p-hydroxyl from p-cresol under non-alkaline conditions via catalytic oxidation. This method eliminates the need for excess acid to neutralize residual alkali in the reaction system and avoids the presence of p-hydroxyl in sodium salt form, thus simplifying the subsequent product separation and purification process. Furthermore, it avoids the generation of large quantities of low-value byproduct salts, significantly reducing the requirements for reaction equipment. The method abandons flammable, explosive, and low-boiling-point methanol as the reaction solvent, instead employing a more stable and safer ethylene glycol (acetonitrile) / acetic acid / water mixed solvent system. Under shorter reaction times and lower reaction temperatures, the conversion rate of p-cresol can reach 100%, and the yield of p-hydroxyl can reach as high as 99%. This method achieves highly efficient conversion of p-cresol to p-hydroxyl and has significant potential for promotion and application in the field of p-hydroxyl preparation technology. Attached Figure Description

[0046] Figure 1 TEM image of PtFe / C catalyst; Figure 2 XPS spectrum of PtFe / C catalyst; Figure 3 XRD pattern of PtFe / C catalyst; Figure 4 Pd under 500℃ heat treatment NP Fine spectrum of Pd 3d electron binding energy in XPS spectra of / SC catalyst; Figure 5 The Pd prepared in Example 3 NP TEM image of the / SC catalyst; Figure 6 The smaller Pd particle size obtained in Example 2 NP HAADF-STEM image of / SC catalyst; Figure 7The XRD patterns of the Pd / SC catalysts obtained at different heat treatment temperatures in Examples 2 to 5 are shown. Figure 8 For Pd NC HAADF-STEM image of / SC catalyst; Figure 9 For Pd NC XPS spectra of the / SC catalyst; Figure 10 HAADF-STEM image of Pd1 / SC catalyst; Figure 11 In the study of batch reaction processes, PtFe / C and Pd NC The graph shows the reactant conversion and product yield results after 5 cycles of using the / SC catalyst; Figure 12 PtFe / C and Pd NC The graph shows the changes in reactant conversion and product yield at the reactor outlet during the evaluation of the / SC catalyst in a continuous batch reactor. Detailed Implementation

[0047] The following description, with reference to preferred embodiments, illustrates the implementation of the present invention. Those skilled in the art can easily understand other advantages and effects of the present invention from the content disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and various details in this specification can be modified or changed based on different viewpoints and applications without departing from the spirit of the present invention. It should be understood that the preferred embodiments are merely illustrative of the present invention and not intended to limit the scope of protection of the present invention.

[0048] Where specific techniques or conditions are not specified in the detailed embodiments, they shall be performed in accordance with the techniques or conditions described in the literature in this field or in accordance with the product instructions. Reagents or instruments whose manufacturers are not specified are all commercially available conventional products.

[0049] The preparation method of PtFe / C catalyst includes the following steps: S1. Dissolve 0.5 mmol of FeSO4·7H2O in 15 mL of deionized water to obtain an iron salt solution; S2. Dissolve 1.5 mmol of 2,2'-bipyridine in 15 mL of ethanol to obtain a pyridine solution; S3. Mix the iron salt solution obtained in S1 and the pyridine solution obtained in S2 to form a deep red [Fe(bpy)3]SO4. Stir overnight at room temperature to obtain a complex solution. S4. Add 0.5 mmol of H2PtCl6·6H2O solution to the complex solution obtained in S3, stir at room temperature for 5 h, and centrifuge at 10000 rpm for 10 min to obtain a red precipitate; wash the red precipitate several times with ethanol, centrifuge to obtain a solid precipitate; dry the solid precipitate in an oven at 40 ℃ overnight; grind the dried precipitate to obtain the PtFe compound; S5. The PtFe compound obtained in S4 was dispersed in 50 mL of deionized water, then sonicated for 20 min, stirred for 2 h, and 2385 mg of activated carbon was added. After mixing for 2 hours, the mixture was dried overnight at 40 °C to obtain the mixture. S6. The mixture obtained in S5 is placed in a mixed atmosphere of hydrogen and argon (hydrogen volume percentage is 5 vol%), heated to 700 °C at a heating rate of 5 °C / min, and heat-treated for 6 h to obtain the PtFe / C catalyst.

[0050] Pd NP The preparation method of / SC catalyst includes the following steps: S1. Preparation of SC support by cobalt-assisted carbonization of molecular precursors: In the synthesis, 2 g of 2,2-dithiophene, 2 g of SiO2 and 1 g of Co(NO3)2·6H2O were added to 150 mL of tetrahydrofuran solution and stirred at room temperature for 6 hours to form a homogeneous mixture. The solvent was then removed by rotary evaporation, dried, and ground to obtain powder. The powder was carbonized for 2 hours at a temperature of 800 °C, a heating rate of 5 °C / min and an N2 atmosphere to obtain carbonized product. The carbonized product was etched alkaline with 2 M NaOH for 3 days, then continuously heated with 0.5 M H2SO4 at a temperature of 90 °C for 6 hours, and then dried overnight at a temperature of 85 °C to obtain mesoscopic SC support. S2. Disperse 100 mg of the mesoscopic SC support obtained in S1 in 20 mL of deionized water, then add 0.0376 mmol of PdCl2 solution, sonicate for 1 hour, stir the suspension vigorously for 12 hours, remove the solvent by rotary evaporation to obtain the precursor. S3. The precursor obtained in S2 was placed in a mixed atmosphere of hydrogen and argon (hydrogen volume percentage 5 vol%), and heated to 450 °C at a heating rate of 5 °C / min for 3 h to obtain a 4 wt.% Pd nanoparticle catalyst. NP / SC.

[0051] Pd NP The preparation method of / SC catalyst includes the following steps: S1. Preparation of SC support by cobalt-assisted carbonization of molecular precursors: In the synthesis, 2 g of 2,2-dithiophene, 2 g of SiO2 and 1 g of Co(NO3)2·6H2O were added to 150 mL of tetrahydrofuran solution and stirred at room temperature for 6 hours to form a homogeneous mixture. The solvent was then removed by rotary evaporation, dried, and ground to obtain powder. The powder was carbonized for 2 hours at a temperature of 800 °C, a heating rate of 5 °C / min and an N2 atmosphere to obtain carbonized product. The carbonized product was etched alkaline with 2 M NaOH for 3 days, then continuously heated with 0.5 M H2SO4 at a temperature of 90 °C for 6 hours, and then dried overnight at a temperature of 85 °C to obtain mesoscopic SC support. S2. Disperse 100 mg of the mesoscopic SC support obtained in S1 in 20 mL of deionized water, then add 0.0376 mmol of PdCl2 solution, sonicate for 1 hour, stir the suspension vigorously for 12 hours, remove the solvent by rotary evaporation to obtain the precursor. S3. The precursor obtained in S2 was placed in a mixed atmosphere of hydrogen and argon (hydrogen volume percentage 5 vol%), and heated to 500 °C at a heating rate of 5 °C / min for 3 h to obtain a 4 wt.% Pd nanoparticle catalyst. NP / SC.

[0052] Pd NC The preparation method of / SC catalyst includes the following steps: S1. Preparation of SC support by cobalt-assisted carbonization of molecular precursors: In the synthesis, 2 g of 2,2-dithiophene, 2 g of SiO2 and 1 g of Co(NO3)2·6H2O were added to 150 ml of tetrahydrofuran solution and stirred at room temperature for 6 hours to form a homogeneous mixture. The solvent was then removed by rotary evaporation, dried, and ground to obtain powder. The powder was carbonized for 2 hours at a temperature of 800 °C, a heating rate of 5 °C / min and an N2 atmosphere to obtain carbonized product. The carbonized product was etched alkaline with 2 M NaOH for 3 days, then continuously heated with 0.5 M H2SO4 at a temperature of 90 °C for 6 hours, and then dried overnight at a temperature of 85 °C to obtain mesoscopic SC support. S2. Disperse 100 mg of the mesoscopic SC support obtained in S1 in 20 mL of deionized water, then add 0.0376 mmol of PdCl2 solution, sonicate for 1 hour, stir the suspension vigorously for 12 hours, remove the solvent by rotary evaporation to obtain the precursor. S3. The precursor obtained in S2 was placed in a mixed atmosphere of hydrogen and argon (hydrogen volume percentage 5 vol%), and heated to 350 °C at a heating rate of 5 °C / min for 3 h to obtain a 4 wt.% Pd fully exposed sub-nano cluster catalyst. NC / SC.

[0053] The preparation method of Pd1 / SC catalyst includes the following steps: S1. Preparation of SC support by cobalt-assisted carbonization of molecular precursors: In the synthesis, 2 g of 2,2-dithiophene, 2 g of SiO2 and 1 g of Co(NO3)2·6H2O were added to 150 mL of tetrahydrofuran solution and stirred at room temperature for 6 hours to form a homogeneous mixture. The solvent was then removed by rotary evaporation, dried, and ground to obtain powder. The powder was carbonized for 2 hours at a temperature of 800 °C, a heating rate of 5 °C / min and an N2 atmosphere to obtain carbonized product. The carbonized product was etched alkaline with 2 M NaOH for 3 days, then continuously heated with 0.5 M H2SO4 at a temperature of 90 °C for 6 hours, and then dried overnight at a temperature of 85 °C to obtain mesoscopic SC support. S2. Disperse 100 mg of the mesoscopic SC support obtained in S1 in 20 mL of deionized water, then add 0.0376 mmol of PdCl2 solution, sonicate for 1 hour, stir the suspension vigorously for 12 hours, remove the solvent by rotary evaporation to obtain the precursor. S3. The precursor obtained in S2 was placed in a mixed atmosphere of hydrogen and argon (hydrogen volume percentage of 5 vol%) and heated to 250 ℃ at a heating rate of 5 ℃ / min for 2 h to obtain 4 wt.% Pd single-atom catalyst Pd1 / SC.

[0054] A method for preparing p-hydroxyaldehyde by non-alkaline catalytic oxidation of p-methylphenol includes the following steps; S1. Mix ethylene glycol, acetic acid and water in a mass ratio of 4:4:2 to obtain a mixed reaction solvent; S2. The PtFe / C catalyst prepared in Example 1 and a commercially available Pd / C (10 wt.%) catalyst are mixed in a mass ratio of 1:1 to form a combined catalyst. S3. Add p-cresol to the mixed reaction solvent in S1 to obtain a reaction solution. The concentration of p-cresol in the reaction solution is 50 mmol / L. S4. Add 150 mL of reaction solution from S3 and 2000 mg of combined catalyst from S2 to the reaction vessel. Replace the gas in the reaction vessel with oxygen three times and maintain the pressure in the vessel at 0.5 MPa. The reaction temperature is 90 °C. The four portions are reacted for 1 h, 2 h, 3 h and 4 h respectively to obtain p-hydroxyl. After the reaction is completed, dilute and filter. The conversion rate of the reactants and the yield of the products are determined by high performance liquid chromatography (hereinafter referred to as HPLC).

[0055] A method for preparing p-hydroxyaldehyde by non-alkaline catalytic oxidation of p-methylphenol includes the following steps: S1. Prepare different mixed reaction solvents, as shown in Table 2; S2. The PtFe / C catalyst prepared in Example 1 and a commercially available Pd / C (10 wt.%) catalyst are mixed in a mass ratio of 1:1 to form a combined catalyst. S3. Add p-cresol to different mixed reaction solvents in S1 to obtain reaction solutions. The concentration of p-cresol in the reaction solutions is 50 mmol / L. S4. Add 150 mL of the reaction solution from S3 and 2000 mg of the combined catalyst from S2 to the reaction vessel. After replacing the gas in the reaction vessel with oxygen three times, maintain the pressure in the vessel at 0.5 MPa and the reaction temperature at 90 °C for 4 h to obtain p-hydroxyl. After the reaction is completed, dilute and filter, and determine the conversion rate of the reactants and the yield of the products by HPLC.

[0056] A method for preparing p-hydroxyaldehyde by non-alkaline catalytic oxidation of p-methylphenol includes the following steps; S1. Mix ethylene glycol, acetic acid and water in a mass ratio of 6:3:1 to obtain a mixed reaction solvent; S2. The PtFe / C catalyst prepared in Example 1 and the Pd catalyst prepared in Example 2 NP / SC catalysts are mixed in a mass ratio of 2:1 as a combined catalyst; S3. Add p-cresol to the mixed reaction solvent in S1 to obtain a reaction solution. The concentration of p-cresol in the reaction solution is 50 mmol / L. S4. Add 150 mL of reaction solution from S3 and 1500 mg of combined catalyst from S2 to the reaction vessel. Replace the gas in the reaction vessel with oxygen three times and maintain the pressure in the vessel at 0.5 MPa. The reaction temperature is 100 °C. The four portions are reacted for 1 h, 2 h, 3 h and 4 h respectively to obtain p-hydroxyl. After the reaction is completed, dilute and filter. The conversion rate of reactants and the yield of products are determined by HPLC.

[0057] A method for preparing p-hydroxyaldehyde by non-alkaline catalytic oxidation of p-methylphenol includes the following steps: S1. Prepare different mixed reaction solvents, as shown in Table 4; S2, using the PtFe / C catalyst prepared in Example 1 and the Pd catalyst prepared by heat treatment at 500°C in Example 2. NP / SC catalysts are mixed in a mass ratio of 2:1 as a combined catalyst; S3. Add p-cresol to different mixed reaction solvents in S1 to obtain reaction solutions. The concentration of p-cresol in the reaction solutions is 50 mmol / L. S4. Add 150 mL of the reaction solution from S3 and 1500 mg of the combined catalyst from S2 to the reaction vessel. After replacing the gas in the reaction vessel with oxygen three times, maintain the pressure in the vessel at 0.5 MPa and the reaction temperature at 100 ℃ for 4 h to obtain p-hydroxyl. After the reaction is completed, dilute and filter, and determine the conversion rate of the reactants and the yield of the products by HPLC.

[0058] A method for preparing p-hydroxyaldehyde by non-alkaline catalytic oxidation of p-methylphenol includes the following steps; S1. Mix ethylene glycol, acetic acid and water in a mass ratio of 5:3:2 to obtain a mixed reaction solvent; S2. The PtFe / C catalyst prepared in Example 1 and the Pd catalyst prepared in Example 4 NC / SC catalysts are mixed in a mass ratio of 2:1 as a combined catalyst; S3. Add p-cresol to the mixed reaction solvent in S1 to obtain a reaction solution. The concentration of p-cresol in the reaction solution is 50 mmol / L. S4. Add 150 mL of reaction solution from S3 and 1500 mg of combined catalyst from S2 to the reaction vessel. Replace the gas in the reaction vessel with oxygen three times and maintain the pressure in the vessel at 0.5 MPa. The reaction temperature is 100 °C. The four portions are reacted for 1 h, 2 h, 3 h and 4 h respectively to obtain p-hydroxyl. After the reaction is completed, dilute and filter. The conversion rate of reactants and the yield of products are determined by HPLC.

[0059] A method for preparing p-hydroxyaldehyde by non-alkaline catalytic oxidation of p-methylphenol includes the following steps: S1. Prepare different mixed reaction solvents, as shown in Table 6; S2, using the PtFe / C catalyst prepared in Example 1 and the Pd catalyst prepared in Example 4. NC / SC catalysts are mixed in a mass ratio of 2:1 as a combined catalyst; S3. Add p-cresol to different mixed reaction solvents in S1 to obtain reaction solutions. The concentration of p-cresol in the reaction solutions is 50 mmol / L. S4. Add 150 mL of the reaction solution from S3 and 1500 mg of the combined catalyst from S2 to the reaction vessel. After replacing the gas in the reaction vessel with oxygen three times, maintain the pressure in the vessel at 0.5 MPa and the reaction temperature at 100 ℃ for 4 h to obtain p-hydroxyl. After the reaction is completed, dilute and filter, and determine the conversion rate of the reactants and the yield of the products by HPLC.

[0060] A method for preparing p-hydroxyaldehyde by non-alkaline catalytic oxidation of p-methylphenol includes the following steps; S1. Mix ethylene glycol, acetic acid and water in a mass ratio of 5:3:2 to obtain a mixed reaction solvent; S2. The PtFe / C catalyst prepared in Example 1 and the Pd catalyst prepared in Example 4 NC / SC catalysts are mixed in a mass ratio of 2:1 as a combined catalyst; S3. Add p-cresol to the mixed reaction solvent in S1 to obtain a reaction solution. The concentration of p-cresol in the reaction solution is 50 mmol / L. S4. Add 150 mL of reaction solution from S3 and 1500 mg of combined catalyst from S2 to the reaction vessel. Replace the gas in the reaction vessel with oxygen three times and maintain the pressure in the vessel at 0.5 MPa. React the four portions at 70℃, 80℃, 90℃ and 100℃ for 4 h to obtain p-hydroxyl. After the reaction is completed, dilute and filter, and determine the conversion rate of reactants and the yield of products by HPLC.

[0061] A method for preparing p-hydroxyaldehyde by non-alkaline catalytic oxidation of p-methylphenol includes the following steps; S1. Acetonitrile, acetic acid and water are mixed in a mass ratio of 1:1:1 to obtain a mixed reaction solvent; S2. The PtFe / C catalyst prepared in Example 1 and the Pd1 / SC catalyst prepared in Example 5 are mixed in a mass ratio of 2:1 to form a combined catalyst. S3. Add p-cresol to the mixed reaction solvent in S1 to obtain a reaction solution. The concentration of p-cresol in the reaction solution is 50 mmol / L. S4. Six portions of 150 mL reaction solution from S3 and 1500 mg combined catalyst from S2 were added to the reaction vessel. The gas inside the reaction vessel was replaced with oxygen three times, and the pressure inside the vessel was maintained at 0.5 MPa. The reaction temperature was 100 °C. The six portions were reacted for 1 h, 2 h, 3 h, 4 h, 5 h and 6 h respectively to obtain p-hydroxyl. After the reaction was completed, the product was diluted and filtered. The conversion rate of the reactants and the yield of the products were determined by HPLC.

[0062] A method for preparing p-hydroxyaldehyde by non-alkaline catalytic oxidation of p-methylphenol includes the following steps: S1. Prepare different mixed reaction solvents, as shown in Table 9; S2. The PtFe / C catalyst prepared in Example 1 and the Pd1 / SC catalyst prepared in Example 5 are mixed in a mass ratio of 2:1 to form a combined catalyst. S3. Add p-cresol to different mixed reaction solvents in S1 to obtain reaction solutions. The concentration of p-cresol in the reaction solutions is 50 mmol / L. S4. Add 150 mL of the reaction solution from S3 and 1500 mg of the combined catalyst from S2 to the reaction vessel. After replacing the gas in the reaction vessel with oxygen three times, maintain the pressure in the vessel at 0.5 MPa and the reaction temperature at 100 ℃ for 6 h to obtain p-hydroxyl. After the reaction is completed, dilute and filter, and determine the conversion rate of the reactants and the yield of the products by HPLC.

[0063] A method for preparing p-hydroxyaldehyde by non-alkaline catalytic oxidation of p-methylphenol includes the following steps; S1. Mix ethylene glycol, acetic acid and water in a mass ratio of 5:3:2 to obtain a mixed reaction solvent; S2. The PtFe / C catalyst prepared in Example 1 and the Pd catalyst prepared in Example 4 NC / SC catalysts are mixed in a mass ratio of 2:1 as a combined catalyst; S3. Add p-cresol to the mixed reaction solvent in S1 to obtain a reaction solution. The concentration of p-cresol in the reaction solution is 50 mmol / L. S4. Add 150 mL of reaction solution from S3 and 1500 mg of combined catalyst from S2 to the reaction vessel. Replace the gas in the reaction vessel with oxygen three times, maintain the pressure in the vessel at 0.5 MPa, the reaction temperature at 90 ℃, and react for 4 h to obtain p-hydroxyl. After the reaction is completed, dilute and filter to obtain the combined catalyst. S5. The combined catalyst obtained in S4 is recycled to perform the catalytic reaction in S4 4 times, that is, the catalyst performs a total of 5 catalytic reactions. The reactant conversion rate and product yield of each reaction are determined by HPLC.

[0064] A reaction for the continuous catalytic oxidation of p-cresol to prepare p-hydroxyl includes the following steps: S1. Mix ethylene glycol, acetic acid and water in a mass ratio of 4:4:2, and add p-cresol to obtain a mixed reaction solvent with a p-cresol concentration of 50 mmol / L. S2. The PtFe / C catalyst prepared in Example 1 and the Pd catalyst prepared in Example 4 NC / SC catalysts are mixed in a mass ratio of 2:1 as a combined catalyst; S3. Add 200 mL of the reaction solution from S1 and 1500 mg of the combined catalyst from S2 to a 500 mL continuous stirred tank reactor. Compressed air flows through the main body of the reaction solution at 20 mL / min through the inlet and outlet of the reactor. Add p-cresol solution to the reactor at a rate of 5 mL / min. After passing through the catalyst filtration device, the reaction solution is stably collected through the collection pipe at a rate of 5 mL / min. The reaction temperature in the reactor is controlled at 100 °C, and mechanical stirring is turned on. The reactor is run continuously for 72 h. Every 2 h, the collected reaction solution is diluted and filtered, and the conversion rate of the reactants and the yield of the products are determined by HPLC.

[0065] Comparative Example 1 A method for preparing p-hydroxyaldehyde includes the following steps; S1. Mix ethylene glycol, acetic acid and water in a mass ratio of 6:3:1 to obtain a mixed reaction solvent; S2. Add p-cresol to the mixed reaction solvent in S1 to obtain a reaction solution. The concentration of p-cresol in the reaction solution is 50 mmol / L. S3. Add 150 mL of the reaction solution from S2 and 1000 mg of the PtFe / C catalyst prepared in Example 1 to the reactor. After replacing the gas in the reactor with oxygen three times, maintain the pressure in the reactor at 0.5 MPa and the reaction temperature at 90 °C for 4 h to obtain p-hydroxyl. After the reaction is completed, dilute and filter, and determine the conversion rate of the reactants and the yield of the products by HPLC.

[0066] Comparative Example 2 A method for preparing p-hydroxyaldehyde includes the following steps; S1. Mix ethylene glycol, acetic acid and water in a mass ratio of 6:3:1 to obtain a mixed reaction solvent; S2. Add p-cresol to the mixed reaction solvent in S1 to obtain a reaction solution. The concentration of p-cresol in the reaction solution is 50 mmol / L. S3. Combine 150 mL of the reaction solution from S2 with the Pd obtained in Example 4 alone. NC500 mg of / SC catalyst was added to the reactor. After replacing the gas in the reactor with oxygen three times, the pressure inside the reactor was maintained at 0.5 MPa. The reaction temperature was 90 °C and the reaction was carried out for 4 h to obtain p-hydroxyl. After the reaction was completed, the product was diluted and filtered. The conversion rate of the reactants and the yield of the products were determined by HPLC.

[0067] Comparative Example 3 A method for preparing p-hydroxyaldehyde includes the following steps; S1. Mix ethylene glycol, acetic acid and water in a mass ratio of 6:3:1 to obtain a mixed reaction solvent; S2. Add p-cresol to the mixed reaction solvent in S1 to obtain a reaction solution. The concentration of p-cresol in the reaction solution is 50 mmol / L. S3. Combine 150 mL of the reaction solution from S2 with the Pd obtained in Example 4 alone. NP 500 mg of / SC catalyst was added to the reactor. After replacing the gas in the reactor with oxygen three times, the pressure inside the reactor was maintained at 0.5 MPa. The reaction temperature was 90 °C and the reaction was carried out for 4 h to obtain p-hydroxyl. After the reaction was completed, the product was diluted and filtered. The conversion rate of the reactants and the yield of the products were determined by HPLC.

[0068] Comparative Example 4 A method for preparing p-hydroxyaldehyde includes the following steps; S1. Mix ethylene glycol, acetic acid and water in a mass ratio of 6:3:1 to obtain a mixed reaction solvent; S2. Add p-cresol to the mixed reaction solvent in S1 to obtain a reaction solution. The concentration of p-cresol in the reaction solution is 50 mmol / L. S3. Add 150 mL of the reaction solution from S2 and 500 mg of the Pd1 / SC catalyst prepared in Example 5 to the reactor. After replacing the gas in the reactor with oxygen three times, maintain the pressure in the reactor at 0.5 MPa and the reaction temperature at 90 °C for 4 h to obtain p-hydroxyl. After the reaction is completed, dilute and filter, and determine the conversion rate of the reactants and the yield of the products by HPLC.

[0069] Detection and Analysis 1) The PtFe / C catalyst prepared in Example 1, and the Pd catalyst prepared in Examples 2 and 3 NP / SC catalyst, Pd prepared in Example 4 NC The / SC catalyst and the Pd1 / SC catalyst prepared in Example 5 were characterized by TEM, XPS, and XRD, respectively. The results are as follows: Figures 1 to 10 As shown.

[0070] from Figure 1Analysis revealed that the PtFe / C alloy nanoparticles were spherical, uniformly distributed on the activated carbon support, with an average particle size of 4.7 nm. HRTEM showed a distinct lattice spacing of 0.2544 nm. Figure 1 d), corresponding to the (111) plane of Pt in PtFe / C alloy nanoparticles.

[0071] from Figure 2 Analysis of the XPS spectra confirmed the presence of Pt and Fe elements on the surface of the activated carbon support. Figure 2 a). Furthermore, the presence of adsorbed oxygen was also observed in the XPS measured spectra. The fine XPS spectra of Pt 4f and Fe 2p are shown below. Figure 2 As shown in cd. Pt 4f spectrum ( Figure 2 c) The double peaks at 71.85 and 75 eV can be attributed to Pt. 0 4f 7 / 2 and Pt 0 4f 5 / 2 The electron binding energy, compared to Pt 0 The binding energy shifts to lower energies. (Fe 2p fine spectrum) Figure 2 The double peaks with binding energies of 711.5 and 726.3 eV in d) can be attributed to Fe. 2+ 2p 3 / 2 and 2p 1 / 2 The electron binding energy, compared to Fe 0 The binding energy shifts to higher energies; this phenomenon indicates a significant electronic interaction between Pt and Fe, with Fe valence electrons transferring to Pt to a certain extent, proving the formation of PtFe alloys.

[0072] from Figure 3 Analysis revealed that no diffraction peaks were found in the XRD pattern for pure Fe and Pt nanoparticles. The diffraction peak positions shifted to higher diffraction angles compared to pure Pt nanoparticles, indicating a significant change in lattice spacing between the PtFe alloy and Pt nanoparticles. This further suggests the formation of an ordered nanoparticle alloy between PtFe nanoparticles. Figure 4 The XPS fine spectrum of Pd 3d valence electron binding energies confirmed the presence of Pd in ​​the supported Pd catalyst. The double peaks near valence electron binding energies of 335.7 and 340.8 eV in the Pd 3d fine spectrum correspond to Pd. 0 3D 5 / 2 and 3D 3 / 2 The binding energy peaks near 338.3 and 343.3 eV are attributed to Pd electrons, while the peaks are attributed to Pd electrons. 2+ 3D 5 / 2 and 3D3 / 2 Valence electrons. Analysis of this data indicates that Pd NP In / SC, the 0-valence state of Pd loaded with Pd predominates in the active ingredient.

[0073] from Figure 5 Analysis shows that Pd NP In the catalyst, Pd nanoparticles are uniformly distributed on the sulfur-carbon support, with an average particle size of 3.24 nm. By controlling the catalyst preparation conditions, the particle size of the Pd nanoparticles can be effectively controlled.

[0074] from Figure 6 Analysis shows that Pd NP / SC nanoparticles are uniformly distributed on the SC support, and the average particle size can be reduced to 1.66 nm. By controlling the heat treatment conditions during catalyst preparation, the particle size of Pd nanoparticles can be effectively controlled.

[0075] XRD diffraction peaks are closely related to Pd particle size and loading. Figure 7 The XRD patterns show that, when the Pd nanoparticles, sub-nano clusters, and single Pd atoms are supported on the SC support, only a weak diffraction peak appears around 40° when the Pd nanoparticle size is small; other peaks are absent due to low diffraction intensity. The peak around 40° corresponds to the Pd (111) crystal plane (JCPDS NO.46-1043). As the heat treatment temperature decreases, the intensity of this characteristic diffraction peak gradually weakens, and a relatively broad weak diffraction peak is formed, indicating enhanced Pd dispersion and a reduction in nanoparticle size. Therefore, by controlling the loading amount of Pd in ​​the support, the heat treatment temperature, and the form and amount of heteroatom doping on the support, controllable preparation of Pd from nanoparticle size to fully exposed sub-nano clusters and single Pd atoms can be achieved.

[0076] Figure 8 High-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM) images show that the Pd sub-nano cluster size is reduced to less than 1 nm. Figure 8 Analysis shows that most Pd metal atoms aggregate into sub-nanometer clusters, while a small portion of Pd metal atoms are confined on the carbon support as single atoms (Pd1).

[0077] from Figure 9 XPS full-spectrum analysis confirmed the presence of Pd, C, and S elements in the fully exposed sub-nano clusters of supported Pd. Figure 9 a). Figure 9 (bd) shows the fine XPS spectra of various elements C, S, and Pd. Figure 9The double peaks at 164.1 and 165.3 eV in the fine XPS spectrum of the S 2p valence electrons shown in c can be attributed to S 2p. 3 / 2 and 2p 1 / 2 Electron. Pd 3d fine spectrum ( Figure 9 The double peaks near binding energies of 336.19 and 343.56 eV in d) correspond to Pd 2+ 3D 5 / 2 and 3D 3 / 2 The peak around 341.68 eV can be attributed to Pd valence electrons. 0 3D 5 / 2 Valence electrons. The fine structure spectrum of Pd indicates that Pd... 2+ The active component dominates, a phenomenon attributed to the interaction between surface Pd elements and S elements in the support. This result corresponds to the observation in HAADF-STEM images that Pd mainly exists in sub-nano clusters. By further controlling the loading of Pd elements in the support, the heat treatment temperature, and the form and amount of heteroatom doping on the support, the catalyst preparation method of this invention can enable Pd to exist in the form of single Pd atoms on a doped carbon support, such as... Figure 10 As shown, HAADF-STEM image characterization reveals that confined Pd single atoms are uniformly distributed on the surface of the mesoporous S-doped C material, and no obvious sub-nano clusters of Pd appear on the support surface. NC or nanoparticles P NP Furthermore, the Pd element is uniformly distributed throughout the entire SC carrier.

[0078] 2) Analysis of p-cresol conversion rate and p-hydroxyl yield The conversion rate of p-cresol and the yield of p-hydroxyl were determined by HPLC at different reaction times in Example 6, and the results are shown in Table 1.

[0079] Table 1: p-cresol conversion and p-hydroxyl yield at different reaction times under the action of PtFe / C and commercially available Pd / C combined catalysts. As shown in Table 1, when the PtFe / C catalyst prepared in Example 1 is used in combination with a commercially available Pd / C catalyst, the conversion rate of p-cresol and the yield of p-hydroxyl gradually increase with the extension of reaction time. At a reaction time of 4 h, the reactants have reacted completely, and the product yield reaches 98.1%.

[0080] The conversion rate of p-cresol and the yield of p-hydroxyl were determined by HPLC in different mixed reaction solvents in Example 7, and the results are shown in Table 2.

[0081] Table 2: p-cresol conversion and p-hydroxyl yield under the action of PtFe / C and commercially available Pd / C combined catalysts in different mixed solvents Table 2 shows that the yield of p-hydroxyl varies with different proportions and compositions of the mixed solvent, indicating that the composition of the mixed solvent has a significant impact on the reaction. This example demonstrates that using the optimal mixed solvent composition is beneficial for the safe, stable, and efficient catalytic oxidation of p-cresol to prepare p-hydroxyl. The conversion rate of p-cresol and the yield of p-hydroxyl at different reaction times in Example 8 were determined by HPLC, and the results are shown in Table 3.

[0082] Table 3: PtFe / C, Pd NP / SC (450) o (Prepared by heat treatment) Conversion rate of p-cresol and yield of p-hydroxyl under different reaction times with a combined catalyst. As can be seen from Table 3, Pd prepared under heat treatment at 450 ℃... NP The combined catalyst constructed by SC nanoparticle catalyst and PtFe / C showed that the reactants were completely reacted after 3 h of catalytic reaction, and the product yield reached 90.5% after 4 h as the reaction time was extended.

[0083] The conversion rate of p-cresol and the yield of p-hydroxyl were determined by HPLC under the action of the combined catalyst in Example 9 in different proportions of mixed solvent. The results are shown in Table 4.

[0084] Table 4: PtFe / C, Pd NP p-cresol conversion and p-hydroxyl yield in different mixed solvents under the action of / SC combined catalyst As shown in Table 4, the yield of p-hydroxyl varies with different proportions and compositions of mixed solvents. Selecting a suitable proportion of mixed solvents is beneficial for the efficient and stable conversion of p-cresol to p-hydroxyl under the action of combined catalysts.

[0085] The conversion rate of p-cresol and the yield of p-hydroxyl under different reaction times in Example 10 were determined by HPLC, and the results are shown in Table 5.

[0086] Table 5: PtFe / C, Pd NC Conversion rate of p-cresol and yield of p-hydroxyl under different reaction times under the action of / SC combined catalyst As can be seen from the analysis in Table 5, the Pd obtained after heat treatment at 350 ℃ NC / SC sub-nano cluster catalyst and PtFe / C form a combined catalyst. After participating in the catalytic reaction for 3 h, the reactants are completely reacted. With the extension of reaction time, the product yield can reach 99.8% after 4 h.

[0087] The conversion rate of p-cresol and the yield of p-hydroxyl were determined by HPLC under different mixed solvents with the combined catalyst in Example 11. The results are shown in Table 6.

[0088] Table 6: PtFe / C, Pd NC p-cresol conversion and p-hydroxyl yield in different mixed solvents under the action of / SC combined catalyst As shown in Table 6, the yield of p-hydroxyl varies with different proportions and compositions of mixed solvents. Selecting a suitable proportion of mixed solvents is beneficial for the efficient and stable conversion of p-cresol to p-hydroxyl under the action of combined catalysts.

[0089] The conversion rate of p-cresol and the yield of p-hydroxyl were determined by HPLC at different reaction temperatures using the combined catalyst in Example 12. The results are shown in Table 7.

[0090] Table 7. PtFe / C, Pd NC p-Cresol Conversion and p-Hydraldehyde Yield at Different Reaction Temperatures under the Action of / SC Combined Catalyst As can be seen from the analysis of Table 7, the same combination of catalysts exhibits significantly different effects at different reaction temperatures. As the temperature increases, the conversion rate of p-cresol gradually increases, and the yield of p-hydroxyl also gradually increases. When the reaction temperature reaches 100℃, the conversion rate of p-cresol and the yield of p-hydroxyl reach their highest values, indicating that increasing the reaction temperature is beneficial to increasing the reaction rate, and the product selectivity does not decrease.

[0091] The conversion rate of p-cresol and the yield of p-hydroxyl were determined by HPLC under the action of the combined catalyst at different reaction times in Example 13, and the results are shown in Table 8.

[0092] Table 8: Conversion rate of p-cresol and yield of p-hydroxyl under different reaction times with PtFe / C and Pd1 / SC combined catalysts As can be seen from Table 8, the combined catalyst consisting of the Pd1 / SC single-atom catalyst obtained by heat treatment at 250 ℃ and the PtFe / C catalyst achieved a reactant conversion rate of 96.7% and a product yield of 78.9% after participating in the catalytic reaction for 6 h.

[0093] The conversion rate of p-cresol and the yield of p-hydroxyl were determined by HPLC in different mixed solvents under the action of the combined catalyst in Example 14. The results are shown in Table 9.

[0094] Table 9: Conversion rate of p-cresol and yield of p-hydroxyl in different mixed solvents under the action of PtFe / C and Pd1 / SC combined catalysts As shown in Table 9, the conversion rate of p-cresol and the yield of p-hydroxyl vary depending on the mixed solvent. This example illustrates that using the optimal mixed solvent composition is beneficial for the safe, stable, and efficient catalytic oxidation of p-cresol to prepare p-hydroxyl.

[0095] The conversion rate of p-cresol and the yield of p-hydroxyl were determined by HPLC after five repeated cycles of the combined catalyst in Example 15. The results are as follows: Figure 11 As shown.

[0096] from Figure 11 Analysis shows that, in five cycles of the experiment, the combined catalyst maintained a high conversion rate of p-cresol and a yield of p-hydroxyl under optimal conditions, demonstrating excellent stability. This proves that the combined catalyst of the present invention is not prone to loss of metal active components and is not prone to poisoning of active sites.

[0097] PtFe / C and Pd were determined by HPLC in Example 16. NC The reactant conversion and product yield at the outlet of the / SC combined catalyst during continuous catalytic oxidation are shown in the following results: Figure 12 As shown.

[0098] from Figure 12 Analysis shows that, in an atmospheric pressure continuous reactor using continuously flowing air as the oxidant, this catalytic system further achieves the continuous production of p-hydroxyl with high selectivity from p-cresol. During the continuous oxidation process, the selectivity of the target product for hydroxyl at the reactor outlet remains above 91% for 72 hours, and the catalyst shows no significant deactivation during continuous use for 72 hours.

[0099] HPLC analysis was performed on Control Example 1 using PtFe / C catalyst alone and Control Example 2 using Pd catalyst alone. NC / SC catalyst, Pd used alone in Comparative Example 3 NP The conversion rates of p-cresol and the yield of p-hydroxyl in Example 4 using the Pd1 / SC catalyst alone are shown in Table 10.

[0100] Table 10 shows the use of PtFe / C catalyst alone or Pd... NC / SC catalyst p-cresol conversion and p-hydroxyl yield Analysis of Table 10 shows that using PtFe / C catalyst alone or Pd alone... NC / SC catalyst or Pd NP The / SC catalyst or Pd1 / SC catalyst exhibits very low conversion rates of p-cresol and p-hydroxyl yields, thus demonstrating the synergistic effect of the combined catalyst of the present invention.

[0101] In summary, the combined catalyst of this invention can efficiently activate molecular oxygen and achieve the conversion of p-cresol to p-hydroxyl with high selectivity, avoiding the self-polymerization of phenolic oxygen rings into uncontrollable polymers and reducing the generation of tar-like substances that may poison the active site of the catalyst. The reaction conditions are simple and easy to control, achieving a highly selective catalytic oxidation of p-cresol to p-hydroxyl under non-alkaline conditions at relatively low pressure (0.5 MPa) and temperature (90-100 °C) and within a short time (3-6 hours). Furthermore, this combined catalyst maintains high p-cresol conversion and p-hydroxyl yield even during repeated use, demonstrating excellent stability.

[0102] This invention provides a method for preparing p-hydroxyl from p-methylphenol by non-alkaline catalytic oxidation. The method is carried out in a stable and safe mixed solvent system free of methanol and soluble bases. This method achieves efficient and convenient preparation of PtFe / C catalysts, as well as Pd single-atom Pd1 / SC and Pd sub-nano clusters with controllable loading and particle size. NC / SC, Pd nanoparticles Pd NP / SC catalyst. Through adsorption regulation of active sites in each intermediate stage and the synergistic effect of each oxidation step, this method activates molecular oxygen to oxidize p-cresol under completely alkali-free conditions. This not only reduces the requirements and risks of reaction equipment but also decreases the cost of subsequent product separation and purification, and avoids the generation of large amounts of low-value waste salt. It has significant potential for widespread application in the field of p-hydroxyl preparation technology.

[0103] The above embodiments are merely preferred embodiments provided to fully illustrate the present invention, and the scope of protection of the present invention is not limited thereto. Equivalent substitutions or modifications made by those skilled in the art based on the present invention are all within the scope of protection of the present invention.

Claims

1. The application of a combined catalyst, characterized in that, The combined catalyst consists of a PtFe / C catalyst and a Pd / SC catalyst; the Pd / SC catalyst is selected from Pd... NC / SC catalyst and Pd NP At least one of / SC catalysts; The support for the Pd / SC catalyst is a mesoscopic SC support obtained by using a cobalt-assisted carbonization molecular precursor system. The combined catalyst is used to catalyze the preparation of p-hydroxyaldehyde from p-cresol under non-alkaline conditions. The PtFe / C catalyst is an ordered nano-alloy catalyst. Pd NC This represents a fully exposed subnanometer cluster of Pd, Pd NP This refers to Pd nanoparticles; The method for preparing p-hydroxyaldehyde by the combined catalyst under non-alkaline conditions through the catalytic oxidation of p-methylphenol includes the following steps: p-Cresol and the aforementioned combined catalyst are added to a mixed solvent that does not contain methanol or soluble base, and the mixture is heated under oxygen or air pressure of 0.3 MPa to 0.8 MPa to obtain p-hydroxyaldehyde; The mixed solvent, which is free of methanol and soluble base, is selected from a mixture of ethylene glycol, acetic acid and water, or from a mixture of acetonitrile, acetic acid and water.

2. The application of the combined catalyst according to claim 1, characterized in that, The mass ratio of the PtFe / C catalyst to the Pd / SC catalyst is 5:1 to 1:

5.

3. The application of the combined catalyst according to claim 1, characterized in that, The preparation method of the PtFe / C catalyst includes the following steps: Iron salts are dissolved in water to obtain an iron salt solution; The pyridine compound is dissolved in an organic solvent to obtain a pyridine solution; The iron salt solution and the pyridine solution were mixed to obtain the complex solution; Platinum acid solution was added to the complex solution to obtain the PtFe compound; PtFe compounds were dispersed in water, then a carbon source was added, the mixture was dried, and subjected to a first heat treatment to obtain a PtFe / C catalyst. And / or, the method for preparing the Pd / SC catalyst includes the following steps: Mesoscopic SC supports were obtained by using a cobalt-assisted carbonization molecular precursor system. The mesoscopic SC support was dispersed in water, and a palladium salt solution was added to obtain the precursor; The precursor was subjected to a second heat treatment to obtain the Pd / SC catalyst.

4. The application of the combined catalyst according to claim 3, characterized in that, The pyridine compound is selected from at least one of pyridine, 2,2'-bipyridine, and 2,2':6',2''-tripyridine; And / or, the iron salt is selected from at least one of ferrous sulfate, ferrous sulfate heptahydrate, ferrous chloride, ferrous nitrate and ferrous acetylacetone; And / or, the carbon source is selected from a carbon material carrier; And / or, the platinum acid solution is selected from at least one of chloroplatinic acid solution, chloroplatinic acid hexahydrate solution, and potassium chloroplatinate solution; And / or, the organic solvent is selected from ethanol; And / or, the palladium salt is selected from at least one of palladium chloride, palladium nitrate, and palladium acetate.

5. The application of the combined catalyst according to claim 3, characterized in that, The temperature of the first heat treatment is 500 ℃~900 ℃, the heating method is programmed heating, and the heating rate is 5 ℃ / min~10 ℃ / min; the time of the first heat treatment is 3 h~6 h; the first heat treatment is carried out in a mixed atmosphere of hydrogen and inert gas. And / or, the temperature of the second heat treatment is 250 ℃~500 ℃, the heating method is programmed heating, and the heating rate is 5 ℃ / min -10 ℃ / min.

6. The application of the combined catalyst according to claim 3, characterized in that, The method for preparing the mesoscopic SC support includes the following steps: adding 2,2-dithiophene, silicon dioxide and cobalt salt to a tetrahydrofuran solution, mixing and drying to obtain a powder; heating and carbonizing the powder, performing alkaline etching and a third heat treatment, and drying to obtain the mesoscopic SC support.

Citation Information

Patent Citations

  • Composite material in atomic dispersion, preparation method thereof and application thereof

    CN109759133A

  • Catalytic system for catalytic oxidation of p-cresol under alkali-free condition and application

    CN114887619A

  • Process for the production of hydroxy-substituted aromatic aldehydes and ketones

    WO2001009072A1